Lectotypification of Streptolirion (Commelinaceae) - Nandikar, Mayur D.; Gurav, Rajaram V. (Phytotaxa, 2015)
In the course of revising the family Commelinaceae in India, it has been found that no type was indicated in the protologue of Streptolirion volubile Edgew. Thus, it warrants typification under execute Art. 9.2 of the International Code of Nomenclature (McNeill & al. 2012). Though not cited explicitly in the protologue, we consider Edgeworth’s own material collected in 1844 from the Indian Himalaya and annotated by him to constitute original material and therefore appropriate for typification. We herein designate a specimen at Kew that unequivocally agrees with the protologue as lectotype.